Time Since Urbanization but Not Encephalisation Is Associated with Increased Tolerance of Human Proximity in Birds - Symonds, Matthew R. E.; Weston, Michael A.; van Dongen, Wouter F. D.; Lill, Alan; Robinson, Randall W.; Guay, Patrick-Jean (Frontiers in Ecology and Evolution, 2016)
The examination of links between a high degree of encephalisation (i.e. large brain mass relative to body size) and the capacity of wildlife to inhabit anthropogenic habitats has formed the basis of several recent studies, although typically they have not uncovered any relationship. It, however, remains unclear whether encephalisation is directly related to a species’ capacity to develop tolerance to human proximity (i.e. a reduction in response to approaching humans). It is also unknown whether such a relationship is related to the size of specific areas of the brain. Using published data on flight-initiation distance (FID), the distance at which animals flee from an approaching human, we estimate the degree of tolerance of human proximity for 42 bird species by comparing FIDs in urban and rural areas, with relatively high and low exposure to humans, respectively. We used a phylogenetic, comparative approach to analyse the relationship of degree of tolerance, and of FID in urban and rural populations more directly, to relative sizes of whole brains (42 species) and brain components (25 species) for the species, and examine the effect of the year that the bird species was first recorded in an urban area (year of urbanisation). We demonstrate an interaction between bird habitat and year of urbanisation on FIDs. Urban populations of species that have a longer history of inhabiting urban areas have lower FIDs (i.e. birds that were urbanised earlier are more tolerant), which may suggest local selection for birds with reduced responsiveness to humans in urban areas. The pattern is not seen in rural populations of the same species, providing additional evidence that it is greater exposure to humans that has resulted in this tolerance. While we found that forebrain mass and optic lobe mass are influential, positive predictors of FID there was no indication that degree of tolerance itself was related to any brain size metric and hence no support for the idea that urban populations of species with larger brains are better able to habituate to human presence. This suggests that processes other than encephalisation explain the high degree of tolerance evident in urban-dwelling birds.